Factors Associated with Energy Efficiency of Focused Ultrasound Through the Skull: A Study of 3D-Printed Skull Phantoms and Its Comparison with Clinical Experiences - Kong, Chanho; Park, So Hee; Shin, Jaewoo; Baek, Hee Gyu; Park, Juyoung; Na, Young Cheol; Chang, Won Seok; Chang, Jin Woo (Frontiers in Bioengineering and Biotechnology, 2021)
While focused ultrasound (FUS) is non-invasive, the ultrasound energy is attenuated by the skull which results in differences in energy efficiency among patients. In this study, we investigated the effect of skull variables on the energy efficiency of FUS. The thickness and density of the skull and proportion of the trabecular bone were selected as factors that could affect ultrasound energy transmittance. Sixteen 3D-printed skull models were designed and fabricated to reflect the three factors. The energy of each phantom was measured using an ultrasonic sound field energy measurement system. The thickness and proportion of trabecular bone affected the attenuation of transmitted energy. There was no difference in the density of the trabecular bone. In clinical data, the trabecular bone ratio showed a significantly greater correlation with dose/delivered energy than that of thickness and the skull density ratio. Currently, for clinical non-thermal FUS, the data are not sufficient, but we believe that the results of this study will be helpful in selecting patients and appropriate parameters for FUS treatment.